Non‐cell‐autonomous function of DR6 in Schwann cell proliferation. (19th February 2018) - Colombo, Alessio; Hsia, Hung‐En; Wang, Mengzhe; Kuhn, Peer‐Hendrik; Brill, Monika S; Canevazzi, Paolo; Feederle, Regina; Taveggia, Carla; Misgeld, Thomas; Lichtenthaler, Stefan F
Abstract: Death receptor 6 (DR6) is an orphan member of the TNF receptor superfamily and controls cell death and differentiation in a cell‐autonomous manner in different cell types. Here, we report an additional non‐cell‐autonomous function for DR6 in the peripheral nervous system (PNS). DR6‐knockout (DR6 KO) mice showed precocious myelination in the PNS. Using an in vitro myelination assay, we demonstrate that neuronal DR6 acts in trans on Schwann cells (SCs) and reduces SC proliferation and myelination independently of its cytoplasmic death domain. Mechanistically, DR6 was found to be cleaved in neurons by "a disintegrin and metalloprotease 10" (ADAM10), releasing the soluble DR6 ectodomain (sDR6). Notably, in the in vitro myelination assay, sDR6 was sufficient to rescue the DR6 KO phenotype. Thus, in addition to the cell‐autonomous receptor function of full‐length DR6, the proteolytically released sDR6 can unexpectedly also act as a paracrine signaling factor in the PNS in a non‐cell‐autonomous manner during SC proliferation and myelination. This new mode of DR6 signaling will be relevant in future attempts to target DR6 in disease settings. Synopsis: The extracellular domain of death receptor 6 can be proteolytically released by the metalloprotease ADAM10 and act as a new paracrine factor negatively influencing myelination in the peripheral nervous system. Function and proteolytic processing of death receptor 6 (DR6) was investigated in the peripheral nervous system (PNS). DR6‐deficient mice show precocious myelination in the PNS. The extracellular domain of DR6 (sDR6) can be proteolytically released from neurons by the metalloprotease ADAM10. sDR6 acts as a new paracrine factor and negatively regulates Schwann cell proliferation and myelination in the PNS. Abstract : Metalloprotease ADAM10 sheds a soluble ectodomain of the orphan TNFR‐family death receptor 6, which regulates myelination in the peripheral nervous system in a paracrine fashion.